The son also rises : surnames and the history of social mobility - Clark, Gregory, 1957- (Princeton economic history of the Western world., 2014)
How much of our fate is tied to the status of our parents and grandparents? How much does this influence our children? More than we wish to believe! While it has been argued that rigid class structures have eroded in favor of greater social equality, The Son Also Rises proves that movement on the social ladder has changed little over eight centuries. Using a novel technique -- tracking family names over generations to measure social mobility across countries and periods -- renowned economic historian Gregory Clark reveals that mobility rates are lower than conventionally estimated, do not vary across societies, and are resistant to social policies. The good news is that these patterns are driven by strong inheritance of abilities and lineage does not beget unwarranted advantage. The bad news is that much of our fate is predictable from lineage. Clark argues that since a greater part of our place in the world is predetermined, we must avoid creating winner-take-all societies --Book jacket.